Β‐Glucan supplementation, allergy symptoms, and quality of life in self‐described ragweed allergy sufferers. Issue 1 (14th December 2012) - Talbott, Shawn M.; Talbott, Julie A.; Talbott, Tracy L.; Dingler, Elaine
Abstract This randomized, placebo‐controlled, double‐blind study compared the effects of daily supplementation for 4 week with 250 mg Wellmune WGP® β‐1, 3/1, 6‐Glucan (WGP) with placebo 250 mg/day (rice flour) on physical and psychological health attributes of self‐described "moderate" ragweed allergy sufferers. Study participants (mean age = 36 ± 9 year; range 18–53 year) were recruited before the beginning of ragweed season (September) in Northeastern Ohio. Serum IgE concentration, allergy symptoms [via self‐report, Visual Analog Scale (VAS), and Rhinoconjunctivitis Quality of Life Questionnaire (RQLQ)], psychological well‐being [Profile of Mood States (POMS)], and physical function (RAND SF‐36 Medical Outcomes Study) were measured immediately prior to and after supplementation with WGP (n = 24) or placebo (n = 24) for 4 weeks. Data were analyzed using repeated measures analyses of variance (ANOVA). Compared with placebo, WGP reduced total allergy symptoms (28%), symptom severity (52%), and symptom rating on the VAS (37%) (P < 0.05), but had no effect on serum IgE levels. As measured by the POMS, WGP increased participants' rating of vigor (10%), but reduced tension (34%), depression (45%), anger (41%), fatigue (38%), and confusion (34%) (P < 0.05). Study participants given WGP reported increased physical health (11%), energy (19%), and emotional well‐being (7%) compared with study participants given the placebo (RAND SF‐36 Medical Outcomes Study). The WGP group also reported decreased sleep problems (53%), reduced nasal symptoms (59%), eye symptoms (57%), non‐nasal symptoms (50%), activities (53%), emotions (57%), and improved quality of life (QOL) (56%), as well as improved global mood state (13%). Supplementation with WGP for 4 weeks improved allergy symptoms, overall physical health, and emotional well‐being compared with placebo in self‐described "moderate" ragweed allergy sufferers during ragweed allergy season.